PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KEPUASAN KERJA PEGAWAI SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAHKABUPATEN PIDIE JAYA - Syarifah Hasnah; Nasir Azis; Sofyan Idris (FEB - Unsyiah, 2018)
The purpose of this research is to know: (1) to describe workload, work environment, competence, job satisfaction and performance of employee (2) influence of work load to employee performance, (3) influence of work environment to employee performance (7) the influence of competence on employee job satisfaction (8) the effect of job satisfaction on employee performance (9) indirect influence of workload on performance of employees through job satisfaction, (10) indirect influence of work environment on employee performance through job satisfaction and (11) indirect influence of competence on employee performance through job satisfaction. This research was conducted at the Regional Secretariat of Pidie Jaya Regency. The object of this research is workload, work environment, competence, employee performance, and job satisfaction with the number of respondents as many as 155 people. The research findings show that workload, work environment, competence, employee performance, and job satisfaction have gone well. The result of research also proves that workload, work environment and competence have an effect on to job satisfaction of employee, then job satisfaction perceived by employee have influence to improve employee performance, workload, work environment and competence influence to employee performance, indirect influence of work load on employee performance through job satisfaction, there is indirect influence of work environment to employee performance through job satisfaction of employee and there is indirect influence of competence to employee performance through job satisfaction of employee